Information literacy instruction: Theory and practice - Þórdís T. Þórarinsdóttir 1947-; Ágústa Pálsdóttir 1955- (2015)
The purpose of the paper is to present and discuss theory of information literacy instruction and its implementation and transfer into practice. Furthermore best practices in the field are brought in and introduced. The methods used are a literature overview and content analysis. In the ever changing world of the present time students in schools and the general public as well need to be equipped with skills to be able to cope with the challenges of the rapid innovations in technology and communication and the rising globalization as well. It is widely recognized that information literacy – the ability to identify information need, seek, locate, critically evaluate and use information in an ethical manner – is among the cornerstones in education and underpins active and informed participation in the information and knowledge society. Iceland does neither have a formal national policy on information literacy nor is information literacy strongly repesented in the National curriculum guidelines for the secondary school. Therefore it is interesting to study the emphasis scholars and other nations place on information literacy for that school level and its instruction as well as the teaching methods and ideology used. Among other the The Big6TM program, introduced by Eisenberg and Berkowitz, is under consideration. The objective of the study is mainly to see if there is a difference between Iceland and other countries concerning the emphasis placed on information literacy and to draw conclusions from the findings.